If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 8x = 3x + 15 Reorder the terms: 5 + 8x = 15 + 3x Solving 5 + 8x = 15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5 + 8x + -3x = 15 + 3x + -3x Combine like terms: 8x + -3x = 5x 5 + 5x = 15 + 3x + -3x Combine like terms: 3x + -3x = 0 5 + 5x = 15 + 0 5 + 5x = 15 Add '-5' to each side of the equation. 5 + -5 + 5x = 15 + -5 Combine like terms: 5 + -5 = 0 0 + 5x = 15 + -5 5x = 15 + -5 Combine like terms: 15 + -5 = 10 5x = 10 Divide each side by '5'. x = 2 Simplifying x = 2
| 50x^2+20x-16=0 | | 6+0.10x=.15x+8 | | 9x-6y=30 | | -(3x-5)-(2x-6)+1=-5(x-1)-(3x+2)+3 | | 8x(7-24)=32 | | 8x(7-24)= | | -2p+120=3p+20 | | 0.5+0.05x=9.8 | | (x-3)(x^2+3x+9)=98 | | 0.5+0.05x=9.6 | | 3x=x+45 | | -14579x-63903= | | 1363x-15942x= | | -35x+1398x= | | 15942x+63903= | | 3d*5e= | | -35x+1373-15995+63210= | | 3cd-2cd= | | 3y=6x+5 | | 2x(2x-3)-(3x-1)(x+1)=-6 | | 9-7-7x-3x=4 | | 5.5p+7=1.5p+35 | | 2X+5-5X=-6+90 | | (x+1)(x-3)=(x+2)(x+2) | | 9-2x-7-13x=5 | | 2x-2+13= | | d^2F=15 | | x^2+9x+448=0 | | (X+4)(X+7)=70 | | y+5=-.454(x+13) | | 3p^2-4p=0 | | 2d+3=7d-1 |